Mechanism of action of cisplatin on Na+/K+ ATPase of Caco-2 colon cells in vitro - Rida Mourad; Rawad Hodeify; Sawsan Kreydiyyeh (PLoS ONE, 2026)
Cisplatin is a chemotherapeutic agent that reverts cancerous cells to the apoptotic route. A decrease in the activity of the Na + /K + ATPase is one of the hallmarks of apoptosis and a major causative factor of the drug-induced nephrotoxicity. Whether cisplatin targets also the colonic ATPase is a question that was addressed in this work using Caco-2 cells as a model. ATPase activity was measured via inorganic phosphate release with and without ouabain, and protein expression was assessed by Western blot. Cisplatin reduced the activity of the Na + /K + ATPase, an effect that was dependent on the transmembrane chloride gradient but had no effect on the purified enzyme, suggesting an indirect action. Fluorescence imaging showed a decrease in the membrane ATPase abundance. Cisplatin was shown to act by increasing intracellular calcium, triggering a sequential activation of p38MAPK and PKA that results in JNK inhibition and a decrease in the Na + /K + ATPase activity.